Socialization of the use of Digital Literacy and Media Literacy for Students of SMPN 3 PAINAN - Ade Irma Suryani; Nila Afriyansih; Yuherman; Erdawati (Asian Journal of Community Services, 2023)
Objective devotion to public This was carried out at Painan 3 Middle School which was aimed at SMPN students with the aim of providing socialization in the use of digital literacy and media literacy in order to prepare an intelligent generation to use digitalization, while the title of this service activity was: Socialization of the use of digital literacy, and literacy media for students of SMPN 3 Painan”. devotion this is implemented so that add understanding Student related: One). Ability to leverage digital literacy, 2). Ability to utilize literacy media. Results Which expected from  Devotion is: 1). Increased Ability to take advantage of digital literacy 2). Increased ability to utilize literacy media , So that the nation's next generation is able to take advantage of digitalization in ease for the challenges of the industrial revolution 4.0 in the future.